The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.7567/jjap.54.04de07
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanical IR thermal detector using torsional oscillation: Improvement of resonator profile for high sensitivity

Abstract: An infrared (IR) thermal detector, which used the torsional oscillation of a micromechanical resonator, was developed to achieve a high sensitivity. The detector has a bimaterial structure consisting of a tense Si film (oscillating body) and a metal film (IR absorber). Owing to the difference in thermal expansion between the two materials, the resonator is bent by light incidence. Because the axis of torsion is bent from the initial flat state, the spring for torsional oscillation hardens and resonant frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The best TCF is ~8% K −1 at an operation temperature of T sub = 45 °C. This TCF is 2 orders of magnitude higher than the best TCF reported so far (~0.1% K −1 ) for IR resonant sensors 25 . In addition, the TCF is more than an order of magnitude higher than resonant temperature sensors 4547 , for which the best reported TCF is 1.7% K −1 .…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…The best TCF is ~8% K −1 at an operation temperature of T sub = 45 °C. This TCF is 2 orders of magnitude higher than the best TCF reported so far (~0.1% K −1 ) for IR resonant sensors 25 . In addition, the TCF is more than an order of magnitude higher than resonant temperature sensors 4547 , for which the best reported TCF is 1.7% K −1 .…”
Section: Resultsmentioning
confidence: 56%
“…The TCF were calculated according to the normalized frequency change within each 5 °C step using the measurements from Figure 2.a. The best TCF is around 8% at the operation temperature of Tsub=45 °C; which is 2 order of magnitude higher than the best TCF reported so far for IR resonant sensors 25 . Since there is a tradeoff between the TCF and Q, the operation temperature of Tsub=45 °C has very high AD value for the integration time τ=500 ms as it is illustrated in Figure 3.b.…”
Section: Smp Resonator Characterizationmentioning
confidence: 65%
See 1 more Smart Citation
“…A number of groups have demonstrated that MEMS/NEMS resonators can work as fast and highly sensitive THz/IR detectors. Depending on the vibrational mode and geometrical shape, they can be categorized as torsional mode [72][73][74][75][76], bending mode [59,77], or membranous shape [57,78,79]. Table 1 provides a survey of the performance of THz/IR detectors based on MEMS/NEMS resonators, allowing for an objective comparison of existing MEMS bolometers.…”
Section: Thz/ir Detection Based On Mems/nems Resonatorsmentioning
confidence: 99%
“…Their use as micromirrors has led to the rapid advances in digital light processing [1]; they have been shown to act as thermal infrared detectors [2,3] and also as resonant mass sensing devices [4,5]. A resonant micropaddle is one such resonant torsional system and has been considered as a potential bio/chemical sensor platform [6,7].…”
Section: Introductionmentioning
confidence: 99%